Partial Replacement of Fine Aggregate Using Mersey Silt (International Journal of Innovative Research in Engineering & Management, 2023)
Numerous researchers are doing  experimental experiments with the goal of identifying  potential eco-friendly, cost-efficient, and efficient cement  substitute materials. The alternatives include recycling,  reusing, and renewing techniques for industrial &  agricultural debris, whereby the advantages might be  acknowledged. By using these wastes as additional and  substitute resources, you may save a lot of energy and use  less cement, which both assist to reduce the amount of  carbon dioxide released into the environment.Any  construction sector needs cement, sand, and aggregate at a  minimum. Sand, a material used in the creation of concrete  and mortar, is crucial in the blend's design. Due to river  erosion and environmental issues, river sand is currently in  limited supply. The structural sector would be affected by  the shortage or absence of sand, thus the most cutting-edge  alternative material must be explored for replacing river  sand so as to prevent excessive river erosion &  environmental harm.Mersey silt is among the most  significant components that many scientists take into  account while discussing other sand-related materials.  Various ratios of this silt combined with sand may be used  to create the necessary concrete mixture. In order to partially  replace natural sand in the manufacturing of concrete, this  work examines the different quantities of Mersey silt. This  research focuses on the compression & split tensile strength  properties of concrete utilising M20 grade concrete  combined with Mersey silt as a partial substitute for natural  sand (10%, 15%, and 20%).
Keywords: Mersey Silt; Fine Aggregate; Concrete